2003
DOI: 10.1097/01.ju.0000067469.01244.5c
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Safety of Laparoscopic Surgery for Urological Malignancy: Experience With More Than 1,000 Operations

Abstract: According to our experience the incidence of local recurrence and the risk of port site metastases is low and seems to be mainly related to the aggressiveness of the tumor and immunosuppression status of the patient, respectively rather than to technical aspects of the laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 19 publications
1
86
0
11
Order By: Relevance
“…LRN sonrası organın nasıl çıkarılacağı konusu tartışmalıdır [24]. Olguların 7'inde nefrektomi materyali organ torbasına (LapSacR, Cook-Europe) yerleştirildikten sonra dijital morselasyon tekniğiy-le, geriye kalan 43 örnekte ise alt batına yapılan 6-8 cm'lik bir insizyondan materyal bir bütün olarak çıkarılmıştır.…”
Section: Discussionunclassified
“…LRN sonrası organın nasıl çıkarılacağı konusu tartışmalıdır [24]. Olguların 7'inde nefrektomi materyali organ torbasına (LapSacR, Cook-Europe) yerleştirildikten sonra dijital morselasyon tekniğiy-le, geriye kalan 43 örnekte ise alt batına yapılan 6-8 cm'lik bir insizyondan materyal bir bütün olarak çıkarılmıştır.…”
Section: Discussionunclassified
“…The safety of laparoscopic and Robotic uro-oncological procedures has already been established [1,2]. Various studies have reported a low incidence of port site metastases after laparoscopic uro-oncological procedures [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established the oncological safety of such minimally invasive procedures for various pelvic malignancies [1,2]. Robot Assisted Radical Cystectomy (RARC) has gained popularity and has shown similar oncological outcomes to open surgery [2].…”
Section: Introductionmentioning
confidence: 99%
“…28,30,34,35 Additionally, Kebebew et al demonstrated that inadvertent laparoscopic resection of clinically unsuspected adrenocortical carcinoma exhibited a high local recurrence rate. 19 Gerber et al reported on their experience with laparoscopic adrenalectomy for lung cancer patients with a solitary metastasis to the adrenal gland.…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%